2010
DOI: 10.3141/2180-08
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Stress Creep and Recovery and Time Sweep Fatigue Tests

Abstract: Crumb rubber modification (CRM) is an effective means of improving neat asphalt performance. Numerous studies have investigated the effects of CRM using the current Superpave® laboratory tests. Recent studies have shown that the assumption of linear viscoelastic behavior or employing insufficient stress or strain levels makes current tests inadequate for properly assessing the performance of binders, especially when modified. This problem has resulted in the development of improved test methods such as the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 8 publications
2
15
0
Order By: Relevance
“…Similar trend was observed for crumb rubber modified asphalt binders by Wasage et al [21]. Higher dosage of crumb rubber could be used to enhance rut resistance of asphalt binder [20]. Considering extreme conditions (25.6 kPa stress and 76°C), VG 30 showed highest J nr (16.9 kPa -1 ) followed by PMB 40 (8.3 kPa -1 ) and CRMB 60 (6.1 kPa -1 ).…”
Section: Comparison Of R For Different Asphalt Binderssupporting
confidence: 65%
See 2 more Smart Citations
“…Similar trend was observed for crumb rubber modified asphalt binders by Wasage et al [21]. Higher dosage of crumb rubber could be used to enhance rut resistance of asphalt binder [20]. Considering extreme conditions (25.6 kPa stress and 76°C), VG 30 showed highest J nr (16.9 kPa -1 ) followed by PMB 40 (8.3 kPa -1 ) and CRMB 60 (6.1 kPa -1 ).…”
Section: Comparison Of R For Different Asphalt Binderssupporting
confidence: 65%
“…Several studies observed better correlation between J nr estimated at 3.2 kPa and rutting performance of asphalt mixes in field and laboratory [10,12,20,21]. However, other studies argued and reported a good correlation between J nr estimated at high stresses and rutting performances of unmodified, SBS modified and/or crumb rubber modified asphalt binders.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This test captures recovery and permanent deformation behavior of binders. Researchers have reported better correlation of non-recoverable creep compliance (J nr ) with rutting performance of asphalt mixes in laboratory as well as in the field [7,8,12]. The J nr is considered to have a better correlation with rutting performance of asphalt mixes compared to G*/sinδ [6,22].…”
Section: Introductionmentioning
confidence: 99%
“…A binder with high G*/sinδ will have lesser dissipated energy, and thus higher rut resistant. The G*/sinδ showed satisfactory results for unmodified binders [6][7][8]. However, this parameter showed unconvincing trend for polymer modified binders due to its inability to capture delayed elastic recovery [6,[9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%